A272 LOSS OF DISEASE TOLERANCE DURING CITROBACTER RODENTIUM INFECTION IS ASSOCIATED WITH IMPAIRED EPITHELIAL DIFFERENTIATION AND HYPERACTIVATION OF T CELL RESPONSES. (1st March 2018) - Kang, E; Zhou, G; Yousefi, M; Xia, J; Gruenheid, S
Abstract: Background: Citrobacter rodentium is an intestinal mouse pathogen widely used as a model to study the mucosal response to infection. Inbred mouse strains suffer one of two fates following infection: self-limiting colitis or fatal diarrheal disease. We previously reported that Rspo2 is a major genetic determinant of the outcome of C. rodentium infection; Rspo2 induction during infection of susceptible mice leads to loss of intestinal function and mortality. Rspo2 induction does not impact bacterial colonization, but rather, impedes the ability of the host to tolerate C. rodentium infection. Aims: To systematically analyze the global gene expression profiles of C. rodentium -infected colon tissues from susceptible and resistant congenic mice strains by deep RNA sequencing to determine the common responses to infection and the Rspo2 -mediated dysfunction pathway signatures associated with loss of disease tolerance. Methods: RNA sequencing was performed on susceptible C3H/HeOuJ (C3Ou) and resistant congenic (C3Ou.B6) mice colons that were either uninfected or infected with C. rodentium for 9 days. We performed differential expression analysis using both edgeR and DESeq2 to assess the shared global response to infection in both strains as well as strain-specific gene expression patterns following infection. Functional enrichment analysis based on KEGG pathways and gene ontology terms were applied to examine the biological roles of modulated differentially expressed genes, which were further incorporated into a high-quality protein-protein interaction network to create network-based gene signatures. Furthermore, gene set enrichment analysis was conducted to investigate the role of Rspo2 in the activation of Wnt signaling, induction of epithelial proliferation, and generation of a poorly differentiated epithelium. Results: Principal component analysis confirmed that samples were closely grouped according to mouse strain and infection status, and that few transcriptomic differences were observed between strains prior to infection. Our results highlighted changes in host metabolism, tissue remodeling, and host defence as common responses to infection. Conversely, increased Wnt and stem cell signatures, loss of epithelial differentiation, and exaggerated CD4 + T cell activation through increased antigen processing and presentation of MHC class II molecules were specifically associated with the response to infection in susceptible mice. Conclusions: Our work provides an unbiased, global perspective of the common and differential host response to infection. We identified novel pathways that were not previously associated with C. rodentium infection and Rspo2 -mediated signaling, hence providing new insights into the underlying mechanisms regulating intestinal homeostasis versus dysfunction. Funding Agencies: CIHRMcGill University Faculty of Medicine